S23 Sensitivity and specificity of radiological findings for non-tuberculous mycobacterium pulmonary disease (NTM-PD) in cystic fibrosis. (December 2018) - Yioe, V; Frost, F; Walshaw, MJ; Wat, D
Abstract : Background: International guidelines recommend changes on CT to help diagnose NTM-PD, including inflammatory nodules, tree-in-bud opacities and cavitation, but many of these also occur in CF lung disease. We were interested to assess the prevalence of these changes and their sensitivity or specificity for NTM-PD in people with CF. Methods: We reviewed the last 114 CT scans performed on people with CF at our large regional adult centre. We recorded their NTM status and compared this with the presence of CT changes, calculating sensitivity and specificity for each CT finding. Results: There were 14 CT scans in people with CF who met the microbiological criteria for NTM-PD. This group were younger (25.2±5.6 years vs 33.8±10.2 years, p=0.003), had lower BMI (20.9±1.9 vs 23.2±4.3 years, p=0.045) and were more frequently colonized with Aspergillus (9/14: 64.3% vs 7/100: 7.0%, p=0.005). Tree-in-bud opacities and inflammatory nodules were more prevalent in NTM-PD (57.1% vs 24.0%, p=0.02% and 50.0% vs 18.0%, p=0.02), but there was no difference for cavities. The sensitivity and specificity for each change are presented in table 1. Conclusion: Tree-in-bud opacities and inflammatory nodules are more frequently in those with recurrent NTM growth but are also common in the CF population at large. Clinicians should consider the sensitivity and specificity of these changes when making a diagnosis of NTM-PD. In the absence of aforementioned changes on CT scans will make the diagnosis of NTM-PD unlikely.